Systems for modern quality and business improvement. Issue 4 (2nd October 2017) - Montgomery, Douglas C.; Borror, Connie M.
Abstract: In 1924 Walter A. Shewhart of the Bell Telephone Laboratories developed the statistical control chart concept. This is usually considered the formal origin of the field of statistical quality control. The control chart is one of the most important technological inventions of the 20th century; it has a simple theoretical foundation, it is easy to use, it can be applied in a wide range of business, service and industrial settings, and it is a proven effective technique in providing the information critical to variability reduction and process improvement. This paper discusses the foundations of Shewhart's work, and his influence on other leaders of the field, including Joseph Juran and W. Edwards Deming. The Shewhart cycle (Plan-Do-Check-Act, or PDCA) was popularized by Deming as a fundamental process improvement paradigm that evolved into the Define-Measure-Analyze-Improve-Control (DMAIC) process that is an integral part of the implementation of modern Six Sigma. Control charts have evolved in many directions beyond the basic Shewhart model, but they remain the key technical component of the field of statistical process control (SPC). We describe how SPC is an integral component of Six Sigma, and the critical role it plays in several steps of the DMAIC process. We conclude with a brief overview of some of the current research in the field.